The Passage of the Bomb Radiocarbon Pulse into the Pacific Ocean - Jenkins, William J; Elder, Kathryn L; McNichol, Ann P; Reden, Karl von (Radiocarbon, 2010)
We report and compare radiocarbon observations made on 2 meridional oceanographic sections along 150°W in the South Pacific in 1991 and 2005. The distributions reflect the progressive penetration of nuclear weapons-produced 14 C into the oceanic thermocline. The changes over the 14 yr between occupations are demonstrably large relative to any possible drift in our analytical standardization. The computed difference field based on the gridded data in the upper 1600 m of the section exhibits a significant decrease over time (approaching 40 to 50‰ in Δ 14 C) in the upper 200–300 m, consistent with the decadal post-bomb decline in atmospheric 14 C levels. A strong positive anomaly (increase with time), centered on the low salinity core of the Antarctic Intermediate Water (AAIW), approaches 50–60‰ in Δ 14 C, a clear signature of the downstream evolution of the 14 C transient in this water mass. We use this observation to estimate the transit time of AAIW from its “source region” in the southeast South Pacific and to compute the effective reservoir age of this water mass. The 2 sections show small but significant changes in the abyssal 14 C distributions. Between 1991 and 2005, Δ 14 C has increased by 9‰ below 2000 m north of 55°S. This change is accompanied overall by a modest increase in salinity and dissolved oxygen, as well as a slight decrease in dissolved silica. Such changes are indicative of greater ventilation. Calculation of “phosphate star” also indicates that this may be due to a shift from the Southern Ocean toward North Atlantic Deep Water as the ventilation source of the abyssal South Pacific.